HEAT REFRACTION AND HEAT-PRODUCTION IN AND AROUND GRANITE PLUTONS IN NORTHEAST ENGLAND - England, P; Oxburgh, E; Richardson, S (1980)
Existing surface heat flow determinations in north-east England indicate a difference in thermal structure between the Alston block of the North Pennines and the coastal regions. New heat flow determinations in the Askrigg block and on the coast support the original indications of higher heat flow in the positive blocks, which are underlain by 400 Myr old granites, than in their marginal sedimentary troughs along the present coastline. Although the two blocks are geophysically and geologically similar, surface heat flow in the Alston block is 300mWm-2 higher than it is in the Askrigg block 50km to its south. Heat flow refraction around high conductivity plutons with high heat production may significantly affect the interpretation of heat flow measurements made on a regional scale but in the present case its effect, if any, is to emphasize the heat flow difference between the two otherwise similar blocks. The chemical differences between the Wensleydale and the Weardale granites - cupolas of the granites underlying the Askrigg and Alston blocks respectively - may be represenative of the granites as a whole and the difference in surface heat flows may result from a contrast in radiogenic head production between the two granites extending to mid-crustal depths.-Authors